Influência do manuseio neonatal sobre os efeitos do estresse emocional e sua interação com fármaco benzodiazepínico em ratos - Boufleur, Nardeli (2012)
Exposure of rodents to stimuli like neonatal handling, have been described to cause behavioral and physiological benefits in adulthood. On the other hand, exposure to adults to stressful environments can result in emotional and neuropsychiatric pathologies. This study aimed to investigate the possible influence of two forms of neonatal handling as tactile stimulation (TS) and maternal separation (MS) on the emotional status of rats exposed to chronic mils stress (CMS) grouped housing, lights on overnight, damp sawdust and others. Furthermore, we aimed to evaluate if neonatal TS could modify anxiolytic effects observed with a low dose of a benzodiazepine drug in adult rats. In the first study, male Wistar pups were submitted daily to TS or MS, from postnatal day one (PND1) to PND21, for 10 min. Unhandled (UH) animails remained in next without any manipulation. In adulthood (PND67), half the animals of each group were exposed to the CMS for 3 weeks and observed in sucrose preference (SP), elevated plus-maze (EPM) and defensive burying test (DBT), followed by euthanasia for biochemical and hormonal assessments. CMS reduced SP, increased anxiety on EPM and DBT and increased adrenal weight. In addition, some parameters of antioxidant defenses in plasma, hippocampus and cortex were altered with exposure to CMS, whereas an increase in protein oxidation in hippocampus and cortex also were observed. In contrast, both forms of neonatal handling were able to prevent changes in SP, anxiety behavior on DBT and adrenal weight CMS-induced. Furthermore, they also prevented alterations in antioxidant defenses in plasma, hippocampus and cortex and protein oxidation in hippocampus. Only TS prevented CMS-induced anxiety symptoms on EPM and protein oxidation in cortex. Furthermore, TS was associated with lower levels of cortisol than in UH rats before and after CMS exposure. Since TS presented better results, we performed a second experiment only with this neonatal handling. In adulthood, the animals received a single administration of diazepam (DZP) (0.25 mg/kg body weight-i.p.) or vehicle (V) and were submitted to behavioral evaluations. DZP treatment reduced anxiety-like behaviors in EPM and increased exploration in EPM, staircase and open field tasks only in TS group. Considering UH animals, DZP treatment only increased exploration in staircase test. TS animals treated with DZP presented reduced anxiety-like behaviors in many parameters of EPM test, increased exploratory behavior in staircase and open field tasks and less immobility in DBT. The results of this study showed the protective role of neonatal handling, especially TS, which may enhance ability to cope with stressful situations in adulthood and affect the response for benzodiazepine substances during this period.